PENERAPAN SISTEM PENGENDALIAN MANAJEMEN DARI PERSPEKTIF LEVERS OF CONTROL DALAM MENINGKATKAN KINERJA ORGANISASI PADANET. BIRO JAWA TIMUR - Catherine Prasetya; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
Implementation of levers of controlhas an influence on organizational performance. The purpose of this research is to know the role of levers of control in order to improve organizational performance in a television industry. This research uses qualitative approach and done by using data collecting technique, interview, observation and also document analysis. The object used in this research is a business entity engaged in the industry of television in East Java. The results of the analysis and discussion show with the application of good levers of control can improve the performance of the organization and bring the business into a better direction. As expressed by Widener (2007) that by integrating the four existing systems, belief system, boundary system, diagnostic control system, and interactive control system, the business strategy can be achieved. Belief systems and interactive control systems motivate members of an organization to seek opportunities for space in more creative, broader way and to be translated as positive energy. Otherwise, to align the positive energy, boundary system and diagnostic control system are used to limit behavior and divert attention translated as negative energy.